The Role of Transvaginal Ultrasonography in the Evaluation of Postmenopausal Bleeding (Delta Medical College Journal, 2024)
Background: Endometrial cancer is currently the most common malignancy of the female genital tract. Most of the women with endometrial cancer initially present with postmenopausal bleeding (PMB) and may be assessed initially with either endometrial biopsy or transvaginal ultrasonography.Objective: The objective of this study was to evaluate transvaginal ultrasound (TVS) measurement of endometrial thickness (ET) in diagnosing endometrial cancer in women with postmenopausal bleeding.Materials and method: This was a prospective study. Transvaginal ultrasonography and Papanicolaou smear were performed in 291 women presenting with postmenopausal bleeding aged >50 years and were followed up for one year in BIRDEM General Hospital from September 2017 to August 2018.Results: One hundred and seventeen women had an endometrial thickness ≤4 mm and one endometrial cancer (0.85%) was diagnosed in this group. Endometrial biopsy was performed in women who had recurrent bleeding. But in women with an endometrial thickness of ≥5mm (174 out of 291 women), endometrial cancer was diagnosed in 9.77%, atypical hyperplasia in 5.17%, ovarian malignancy in 1.72% and total malignancy was 17.8%.Conclusion: Transvaginal ultrasonography using a ≤4 mm cut-off has high sensitivity for detecting endometrial cancer and can identify women with PMB who are highly unlikely to have endometrial cancer, thereby avoiding more invasive endometrial biopsy.Delta Med Col J. Jan 2021;9(2): 91-95